A Review on Artificial Intelligence – Insights from Nursing Care and Implementation in Nursing Education - Alharbi, Mohammad K. (Asian Journal of Pharmaceutics (AJP), 2024)
Artificial intelligence (AI) refers to a digital computer or computer-controlled robot’s ability to do tasks that are generally associated with humans. AI in nursing care can improve clinical decision-making and provide evidencebased care to their patients. Therefore, its implementation in nursing practice and education is essential to further receive the benefits of AI, to the patients and health-care professionals such as nurses and nurse practitioners. The integration of the AI concept has been a key advance in higher education, with the potential to improve education by offering students more tailored and efficient learning experiences. This review provides an overview of AI in nursing care and its benefits of implementation in nursing curriculum.